Baseline monocyte count predicts symptom improvement during intravenous ketamine therapy in treatment-resistant depression: a single-arm open-label observational study - Pedraz-Petrozzi, Bruno; Spangemacher, Moritz; Deicher, Anton; Drews, Lena; Defert, Julie; Silva-Colmenero, Ana Yaiza; Wein, Paul; Riedinger, Elena; Gründer, Gerhard; Gilles, Maria; Sartorius, Alexander; Reinwald, Jonathan R. (Frontiers in Psychiatry, 2024)
Background: Neuroinflammatory processes in depression are associated with treatment resistance to conventional antidepressants. Ketamine is an effective new therapeutic option for treatment-resistant depression (TRD). Its well-established immunomodulatory properties are hypothesized to mediate its antidepressant effect. In this context, higher levels of inflammation may predict a better treatment response. However, conclusive evidence for this hypothesis is lacking. We thus investigated whether standard peripheral inflammatory cell markers and C-reactive protein (CRP) levels could predict symptom improvement during intravenous ketamine therapy in TRD patients. Methods: 27 participants with TRD were treated with six weight-adjusted intravenous ketamine infusions (0.5 mg/kg bodyweight) over three weeks. Baseline assessments included CRP, absolute monocyte count (AMC), and absolute neutrophil count (ANC). Depression severity was measured using the Montgomery-Åsberg Depression Rating Scale (MADRS) at baseline (D1), after the first (D3) and before the last ketamine infusion (D18). Raters were blinded for the baseline laboratory assessments. Results: 13 participants responded to ketamine treatment, and 8 participants partially responded. Baseline AMC showed a strong negative correlation with MADRS change at D3 (r=-0.57, p=0.002) and at D18 (r =-0.48, p=0.010), indicating that a high baseline AMC was associated with greater symptom improvement. A generalized linear model confirmed the association of baseline AMC with symptom improvement during ketamine treatment when additionally accounting for age, sex, and body mass index. Specifically, baseline AMC demonstrated predictive value to discriminate responders and partial responders from nonresponders, but lacked discriminative ability between partial responders and responders. Baseline ANC correlated with the MADRS changes at D3 (r=-0.39, p=0.046), while CRP values did not correlate at all. Conclusions: Our prospective single-arm open-label observational study demonstrated that baseline AMC reliably predicted symptom improvement during intravenous ketamine treatment in TRD patients. AMC could therefore serve as a simple and easily accessible marker for symptom improvement during ketamine therapy in daily clinical practice. Future studies with larger sample sizes and a more detailed longitudinal assessment of AMC subtypes are needed to better understand the specific relationship between monocytes and the neuromodulatory effects of ketamine.